850 hPa Geopotential Height Link with Iraqi Precipitation and Temperature - Jasim Al-Khalidi; Dher Bakr; Rudainah Sedeeq; Lara Faleh (Revista Brasileira de Meteorologia)
Abstract The study examines the connection between the geopotential height (Z850 hPa) and the temperature (°C) and precipitation (mm) in Iraq. The observation data for climatological parameters that are currently available from the Iraqi meteorological organization are used. The temporal analysis of precipitation had a homogeneous data with a single mean for the period but temperatures throughout the research period exhibit a fluctuating tendency, with most stations showing a rising trend after 1993. The northern mountain area of Iraq has the highest amounts of precipitation, while the southern portion of the country records the lowest amounts. The distribution of temperature is characterized in reverse by the precipitation pattern. A correlation map is used for investigating the link between Z850 hPa and the two Iraqi climatological factors. According to the research, cold air descending from the Polar Regions is the primary mechanism responsible for bringing cold air mass over the Iraqi region during winter precipitation. Iraq receives precipitation in the springtime mostly due to the advection of moist air from the Mediterranean Sea and North Africa. Additionally, during summer and autumn, the hot air advection from India and eastern Africa through the Arabian Peninsula is associated with Iraqi temperature patterns.